INTEGRATING POWTOON VIDEO INTO WHATSAPP GROUP CLASS IN TEACHING READING - Ningsih, Nuri Ati (Universitas Mahaputra Muhammad Yamin, 2023)
This research integrates Powtoon videos and WhatsApp group classes to teach reading in Intensive reading subjects. It describes the implementation of Powtoon Video and Whatsapp Group Classes in Intensive Reading classes for English Teaching Department students of Universitas PGRI Madiun during the pandemic era. Descriptive qualitative was chosen as a research method. The subject of this research is the first-semester students of the English Teaching Department consisting of 16 students. The research data were collected through observation and interviews. The collected data was then analyzed through data reduction, data display, and conclusion. The result of this research shows that, in general, the process of online teaching by using Whatsapp Group Class and Powtoon video is conducted into two sections. The first is preparation and the second is implementation. In preparation, the lecturers have to prepare some teaching devices, such as lesson plans, Powtoon video material, YouTube channel, and some rules for conducting the class. The class implementation consists of pre, main /breaking time, and closing activities. The different things in this research are found in the main activities or it’s called breaking time. It’s different from real classroom activities. The class was conducted with extraordinary treatments and in boundless time caused of the low access to internet signal and most of the students live in rural areas. This type of combination makes the students feel comfortable because they can access the material at every time and everywhere. By this situation, it will create a meaningful teaching-learning process, the student’s motivation will appear automatically, and they become a more active and self-individual learner.